A Cross-sectional Study of Group B Streptococcus–Associated Sepsis, Coinfections, and Antibiotic Susceptibility Profile in Neonates in Pakistan. (August 2020) - Asghar, Samra; Khan, Junaid Ali; Mahmood, Muhammad Shahid; Arshad, Muhammad Imran
Abstract : Background: Neonatal sepsis is a leading cause of morbidity and early-life mortality worldwide, and previous data have reported the highest neonatal mortality rate in Pakistan. Purpose: The present study aimed to decipher the prevalence of group B Streptococcus (GBS)–associated sepsis, coinfections, and antibiotic susceptibility of isolated microbes in neonates. Methods: Blood samples of 100 cases of neonatal sepsis were subcultured on blood agar, GBS agar, and MacConkey agar for isolation of GBS and suspected microbes. Results: Of 100 neonatal blood samples, 85 blood samples were culture-positive, including mixed culture growth (n = 18), 25 samples as early-onset neonatal sepsis (EONS) and 60 as late-onset neonatal sepsis (LONS). Staphylococcus aureus showed high percent positivity (31.4%), followed by Candida sp (16.5%), GBS (14.1%), Klebsiella (14.1%), Staphylococcus epidermidis (11.8%), Pseudomonas (9.4%), Acinetobacter (9.4%), Esherichia coli (8.2%), and Enterococcus (5.9%). GBS was isolated more frequently from EONS than from LONS with 50% coinfections. Mode of delivery, gender, and respiratory distress in neonates were significantly associated with culture-positive sepsis. GBS isolates were highly (91.7%) susceptible to vancomycin, cefotaxime, and chloramphenicol, followed by penicillin (83.3%), ampicillin, and tetracycline (75%). GBS isolates were resistant to erythromycin, clindamycin, ciprofloxacin, and linezolid. Implications for Practice: Our findings evidenced GBS-associated risk factors and antibiotic susceptibility pattern of neonatal sepsis, which will help clinicians in management, control, and treatment of neonatal sepsis. Implications for Research: The epidemiological evidence of GBS-associated neonatal sepsis, demographic characteristics, risk factor data analysis, and drug resistance pattern has disease prevention implications in neonates in low-income countries including Pakistan.